[PP.21.14] TYPE A PERSONALITY AS THE PRINCIPAL PSYCHOLOGICAL DETERMINANTS OF LEFT VENTRICULAR MASS INDEX IN HYPERTENSIVE PATIENTS. (September 2017) - Greco, A.; Maloberti, A.; Sormani, P.; Colombo, G.; D'Addario, M.; Magrin, M.E.; Miglioretti, M.; Sarini, M.; Vecchio, L.; Laurent, S.; Boutouyrie, P.; Giannattasio, C.; et al.
Abstract : Objective: Increased Left Ventricular Mass Index (LVMI) is a well known risk factor for cardiac morbidity and mortality. Furthermore, it is widely recognized that clinical evolution and progression of established CV diseases are related to a range of psychological characteristics. Some previous studies evaluated the response to psychological test as a predictor of LVMI with controversial results. Besides this kind of studies, little is known about LVMI and its association with psychological characteristics in arterial Hypertension (HT) patients. The aim of the current cross-sectional study was to evaluate the association between Type A personality, Type D personality, depression, anxiety, perceived stress, and LVMI in a cohort of hypertensive patients, using baseline examination data of the TIPICO project. Design and method: A total of 244 outpatients (ages 18–80 years) followed by the Hypertension Unit of S. Gerardo Hospital (Monza, Italy) affected by essential hypertension were recruited. Anamnestic data, clinical BP, and laboratory data and LVMI were evaluated. Patients were asked to complete a battery of psychological questionnaires under the guidance of a psychologist. The associations between psychological variables and LVMI was explored using multivariate stepwise linear regression analysis and regression coefficients (b) were given per 1-point increment. Results: Mean age was 55.9 ± 10.1 years, SBP and DBP were 135.6 ± 17.7 and 82.5 ± 9.1 mmHg. Factors associated with LVMI in univariate analysis were age, sex, mean blood pressure, pulse pressure, presence of diabetes. The results from the multivariate stepwise linear regression analysis showed that sex (beta = 0.252, p < 0.001), age (beta = 0.135, p < 0.037), mean blood pressure (beta = 0.178, p = 0.003), family history of CV disease (beta = 0.129, p = 0.027), and Type A personality (beta = 0.148, P = 0.014) were significantly and independently associated with LVMI. These associations with LVMI were independent of blood pressure components in multivariate analysis. Conclusions: The current study shows that, among psychological factors, higher levels of Type A personality is related to higher LVMI, while Type D personality, anxiety, depression, perceived stress are not associated with it. Also if in a cross-sectional design, this study seem to suggest that Type A personality play a role in the presence of hypertension.